Library Copywriting - Reut, Anna M. (Bobcatsss, 2023)
Advertising has closely entered the life of modern society and the library was no exception. The better the advertising in library activity is set up, the more users will be interested in this library. The significant element of library advertising, namely copywriting, is investigated by methods of analysis and analogy. Since the topic of library copywriting is little studied, the scientific work spells out a clear definition of its concept and purpose. A distinctive feature of the texts is indicated. The main functions of library copywriting are highlighted: communicative, regulatory and generalizing. Each of them has its own characteristics. There are several types of copywriting, which will be used to some extent in the library, depending on what it will advertise on the information platform. A comparison of rating and its application in the library sphere is given. Popular types of copywriting are identified: exclusive and copyright, their features are analyzed. The tactical and technical methods of library copywriting are considered, thanks to which the text is perceived by the reader easily. As practice shows, the library has the active work of the copywriter, even during the period of information lull. From here follows the question of the importance of studying library copywriting in all its aspects. Since the services of a professional copywriter are costly for the library, all its functions are performed by a librarian. The article contains examples of special applications, services and sites that will help employees form the content, correctly taking into account the spelling and uniqueness of the text. Ortho-online, Advego, Orthographer are services with which you can check the spelling of the text, as well as make semantic analysis. It is described what tool can select synonyms, which will allow the librarian to create unique content. The authors offer such online services as AnalysisPisem.RU and Vaal-mini. The characteristic features of the services, their assistance in compiling a psycholinguistic analysis of the author of the text are described. It was found that with their help the librarian will compile an emotionally colored advertising text. The program Quotania can also be used in library copywriting. It is perfectly suited for promotional presentations. Particular attention is paid to advertising slogans and what dictionary can be used by the library copywriter to select rhymes. To draw the conclusion, one can say that the librarian should not rely only on these services and sites. In order to master the library copywriting, the employee must constantly develop himself. As research on this topic showed, knowledge of library copywriting will help the specialist in many working processes, including transferring their thoughts to printed or electronic media in a correct way. This article will be useful for librarians, culturologists, copywriters and specialists studying aspects of marketing and communication activities. Being currently a relevant issue, library copywriting undoubtedly requires further research. With the in-depth study of copywriting, the library will be able to reach a new level.